(untitled) (European Journal of Marketing and Economics, 2024)
As the world population is aging, Health tourism has become vitally important and will be increased day by day. Because of the availability of quality health services and more favorable prices as well as to shorten the waiting list for medical services regionally and internationally. There are some aspects of managing and doing marketing activities in order for medical tourism to be feasible, in a region called as clustering in a region with main stakeholders groups includes Health providers, Tourism cluster, etc. There are some related and affecting factors to be considered for the feasibility of medical tourism within this study such as competitiveness, clustering, Entrepreneurship, SMEs. One of the growth phenomenon is Health tourism in the city of Izmir and Turkey. The model of five competitive forces of Porter and The Diamond model that is an economical model that shows the four main factors that affect the competitiveness of a nation and its industries in this study. The short literature of medical tourism and regional clustering have been mentioned.